Penerapan Model Pembelajaran Kooperatif Tipe TGT dalam Meningkatkan Hasil Belajar Matematika Siswa Kelas II SD - Rizky, Putri Alva; Rahman, Siti Fasha Srialya; Ramadani, Siti Zulfaa; Blesia, Elisabeth Milka; Hopeman, Teofilus Ardian (STAI Muhammadiyah Paciran Lamongan, 2025)
Abstract This study aims to determine the effectiveness of the Teams Games Tournament (TGT) type cooperative learning model in improving elementary school students' mathematics learning outcomes. The study was conducted at Gudang Elementary School on 19 second-grade students, using the Classroom Action Research (CAR) method for three cycles. The TGT model was chosen because it combines group work and educational games to create an active and enjoyable learning atmosphere. Data were collected through learning outcome tests and documentation. The results showed a significant increase in the average test scores and active participation of students. These findings indicate that the application of the TGT model is effective in improving elementary school students' understanding of mathematical concepts and learning engagement. Keywords: cooperative learning, TGT, learning outcomes, mathematics. Abstrak Penelitian ini bertujuan untuk mengetahui efektivitas model pembelajaran kooperatif tipe Teams Games Tournament (TGT) dalam meningkatkan hasil belajar matematika siswa sekolah dasar. Penelitian dilakukan di SD Negeri Gudang pada siswa kelas II sebanyak 19 orang, menggunakan metode Penelitian Tindakan Kelas (PTK) selama tiga siklus. Model TGT dipilih karena menggabungkan kerja kelompok dan permainan edukatif untuk menciptakan suasana belajar aktif dan menyenangkan. Data dikumpulkan melalui tes hasil belajar dan dokumentasi. Hasil penelitian menunjukkan peningkatan signifikan pada rata-rata nilai tes dan partisipasi aktif siswa. Temuan ini menunjukkan bahwa penerapan model TGT efektif dalam meningkatkan pemahaman konsep matematika dan keterlibatan belajar siswa sekolah dasar. Kata kunci: pembelajaran kooperatif, TGT, hasil belajar, matematika.